Differential branching fraction and angular analysis of Λ0b → Λμ+μ- decays - Aaij, Roel; Adeva, B.; Adinolfi, M.; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Dordei, Francesca; et al. (Journal of high energy physics, 2015)
The differential branching fraction of the rare decay Λb0→ Λμ+μ− is measured as a function of q2, the square of the dimuon invariant mass. The analysis is performed using proton-proton collision data, corresponding to an integrated luminosity of 3.0 fb−1, collected by the LHCb experiment. Evidence of signal is observed in the q2 region below the square of the J/ψ mass. Integrating over 15 < q2 < 20 GeV2/c4 the differential branching fraction is measured asdℬΛb0→Λμ+μ−/dq2=1.18−0.08+0.09±0.03±0.27×10−7GeV2/c4−1, where the uncertainties are statistical, systematic and due to the normalisation mode, Λb0→ J/ψΛ, respectively. In the q2 intervals where the signal is observed, angular distributions are studied and the forward-backward asymmetries in the dimuon (AFBℓ) and hadron (AFBh) systems are measured for the first time. In the range 15 < q2 < 20 GeV2/c4 they are found to beAFBℓ=−0.05±0.09stat±0.03systandAFBh=−0.29±0.07stat±0.03syst.
Im Titel sind "0", "+" und "-" hochgestellt
Im Titel sind "0" und "b" untereinander geschrieben: "0" hochgestellt, "b" tiefgestellt
The LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, B. Adeva, M. Adinolfi, S. Bachmann, A. Bien, J. Blouw, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, F. Dordei, S. Esen, C. Faerber, M. Fontana, D. Gerick, E. Gersabeck, L. Grillo, X. Han, S. Hansmann-Menzemer, A. Jaeger, M. Kolpin, K. Kreplin, G. Krocker, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, J. Neubert, M. Neuner, T. Nikodem, M. Schmelling, P. Seyfert, M. Stahl, S. Stahl, U. Uwer, M. Vesterinen, R. Waldi, S. Wandernoth, D. Wiedner, A. Zhelezov [und 662 weitere]
Gesehen am 08.10.2020